2019
DOI: 10.1097/pas.0000000000001229
|View full text |Cite
|
Sign up to set email alerts
|

Small and Isolated Immunohistochemistry-positive Cells in Melanoma Sentinel Lymph Nodes Are Associated With Disease-specific and Recurrence-free Survival Comparable to that of Sentinel Lymph Nodes Negative for Melanoma

Abstract: Although immunohistochemistry (IHC) has improved our ability to detect melanoma metastases in sentinel lymph nodes (SLN), the American Joint Committee on Cancer (AJCC) does not provide a lower threshold for determining if a SLN is positive for metastasis. Existing literature suggests that even a small aggregate or an enlarged, abnormal cell detectable by IHC can be associated with an adverse outcome. In our experience, however, some SLNs contain small solitary cells the size of neighboring lymphocytes demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…In these cases, and in particular secondary to the use of immunohistochemical stains as an adjunct to H&E when evaluating sentinel lymph nodes, an increasing number of cases showing only ITCs or minute foci of tumor are increasingly recognized. The true clinical significance of these findings and their implications in subsequent patient management vary depending on the organ system and tumor type being evaluated (35)(36)(37)(38).…”
Section: Lymph Node Metastases In Endometrial Carcinomamentioning
confidence: 99%
“…In these cases, and in particular secondary to the use of immunohistochemical stains as an adjunct to H&E when evaluating sentinel lymph nodes, an increasing number of cases showing only ITCs or minute foci of tumor are increasingly recognized. The true clinical significance of these findings and their implications in subsequent patient management vary depending on the organ system and tumor type being evaluated (35)(36)(37)(38).…”
Section: Lymph Node Metastases In Endometrial Carcinomamentioning
confidence: 99%
“…As these lymph nodes are typically clinically negative, most of the metastases detected will be occult and/or ultra-low volume disease. The significance of ultra-low volume disease is uncertain, with variable results in the literature possibly relating to how the finding of isolated cells detected by immunohistochemistry is interpreted 7 11. The most recent American Joint Committee on Cancer (AJCC) staging guide does not provide a low end threshold at which metastatic melanoma is considered clinically relevant, allowing for even single cells to be considered as equivalent to a positive lymph node.…”
Section: Sentinel Lymph Node Mapping: the Melanoma And Breast Cancer mentioning
confidence: 99%
“…A recent study found that, in such cases, attention should be paid to the morphology of the cells. Those that are morphologically similar to the primary melanoma, even when present as single cells or small cell groups (ie, ≤0.2 mm), are associated with decreased survival compared with negative sentinel lymph nodes, although this association with decreased survival increases with the size of the metastasis 11. It is impracticable to optimize a sentinel lymph node ultra-staging protocol to detect single-cell metastases, and any proposed protocol must balance clinical relevance with resources of the pathology laboratory and the pathologist.…”
Section: Sentinel Lymph Node Mapping: the Melanoma And Breast Cancer mentioning
confidence: 99%